Assessment and influence of a training program aimed to improve the motivational climate transmitted by basketball coaches - C. Conde; B. J. Almagro; P. Sáenz-López; A. Domínguez; J. A. Moreno-Murcia (Asociación Española de Ciencias del Deporte, 2010)
The aim of this work was to analyze and compare the influence of the investigatory training program about a transmitted motivational climate for basketball coaches. The sample comprised of five basketball coaches (aged between 26 and 32), two of them participated in a investigatory training program. The behavior of the coaches was analyzed with an adaptation of the Coaching Behavior Assessment System (Smith, Smoll, and Hunt, 1977). It was realized by six observations within three months and was applied with two coaches of the investigatory training program, which approaches the established premises by Ames (1922) under the name TARGET. The results of the observations show how those progressed in increasing the transmission of the task climate, while the two coaches of the control group did not improve. In conclusion, we want to highlight the necessity of promoting a motivational climate in a task, furthermore the importance of the training programs, because the recommendations, which were given, helped the coaches to make the training an enjoyable and positive experience. Key Words: Intervention, motivation, training program, coaches